2023
DOI: 10.1038/s41598-023-38804-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in time course and diagnostic accuracy of GFAP and UCH-L1 in trauma patients with mild traumatic brain injury

Abstract: Glial Fibrillary Acidic Protein (GFAP) and Ubiquitin C-terminal hydrolase (UCH-L1) have been FDA-approved for clinical use in mild and moderate traumatic brain injury (TBI). Understanding sex differences in their diagnostic accuracy over time will help inform clinical practice. We sought to evaluate the sex differences in the temporal profile of GFAP and UCH-L1 in a large cohort of trauma patients presenting to the emergency department. To compare the biomarkers’ diagnostic accuracy in male versus female patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…A recent study displayed higher concentrations of UCH-L1 in male patients compared to female, while similar findings were not found with GFAP. Regardless of these findings, the overall diagnostic precision did not significantly differ between sex groups [ 46 ]. Although there are differences in age and sex between our groups, their distribution reflects the general population and epidemiology of stroke, with older age and female sex linked to a worse burden of stroke mortality and disability [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study displayed higher concentrations of UCH-L1 in male patients compared to female, while similar findings were not found with GFAP. Regardless of these findings, the overall diagnostic precision did not significantly differ between sex groups [ 46 ]. Although there are differences in age and sex between our groups, their distribution reflects the general population and epidemiology of stroke, with older age and female sex linked to a worse burden of stroke mortality and disability [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…GFAP is an intermediate filament protein that is highly specific for cells of astroglial lineage [56]. It is known as an astroglial marker of injury and is found in the astroglial skeleton of both white and gray brain matter [57]. It is also expressed by the Leydig cells of the testes [58].…”
Section: Glial Fibrillary Acidic Protein (Gfap)mentioning
confidence: 99%
“…Accumulating studies on TBI have shown sensitive biomarkers to determine the severity of the disease. Foremost are inflammatory biomarkers such as GFAP and UCH-L1 [84,85], which can be assayed in blood samples from TBI patients. For each sample draw, a single vial of approximately 2 mL of blood is collected and placed in serum separator tubes allowing it to clot at room temperature.…”
Section: Inflammation (Gfap and Uch-l1)mentioning
confidence: 99%